Dialogical Principles for Qualitative Inquiry: A Nonfoundational Path. Issue 1 (February 2014) - Pozzebon, Marlei; Rodriguez, Charo; Petrini, Maira
Leaving the thesis proposal defense room, the PhD business student had an important assignment to accomplish before being authorized to set a date for defending her thesis: to better justify the validity of her qualitative inquiry framed by a critical interpretive standpoint. Knowing that the generation, analysis, and interpretation of empirical materials are processes always conducted within some understanding of what constitutes legitimate inquiry and valid knowledge, she drew inspiration from ethnographical, confessional, critical, and post-modern work to propose a set of dialogical principles for conducting and evaluating a nonfoundational type of research inquiry. This manuscript revisits this venture a number of years later, reflecting on what has changed and what is still missing. We argue that there is a space and an occasion in the research methods literature for proposing dialogical principles for nonfoundational research, principles that are particularly relevant for qualitative researchers struggling in business schools worldwide.